Design and development of a biomimetic jellyfish robot that features ionic polymer metal composites cituators - Akle, Barbar (2011)
This paper presents the design, fabrication, and characterization of a second generation biomimetic jellyfish robot that uses ionic polymer metal composites (IPMCs) as flexible actuators for propulsion. The shape and swimming style of this underwater vehicle are based on the Aurelia aurita jellyfish, which has an average swimming speed of 13 mm/s and which is known for a high swimming efficiency. The critical components of the vehicle include the flexible bell that provides the overall shape and dimensions of the jellyfish, a central hub used to provide electrical connections and mechanical support to the actuators, and flexible IPMC actuators that extend radially from the central hub. In order to provide increased shape holding ability and reduced weight, the bell is fabricated from a commercially available heat-shrinkable polymer film. A new lightweight hub has been designed and was fabricated by 3D printing using ABS plastic material. The hub features internal electrical contacts for providing voltage to the individual IPMC actuators. Finally, a new set of IPMC actuators are manufactured using the Direct Assembly Process (DAP). The IPMC actuators constructed for this study demonstrated peak-to-peak strains of ∼ 0.7% in water across a frequency range of 0.1–1.0Hz. By tailoring the applied voltage waveform and the flexibility of the bell, the completed robotic jellyfish swam at maximum speed of 1.5 mm/s.